2012
DOI: 10.1186/1471-227x-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Acute traumatic coagulopathy among major trauma patients in an urban tertiary hospital in sub Saharan Africa

Abstract: BackgroundMortality from trauma remains a major public health issue as it is the leading cause of death in persons aged 5 to 44 years .Uncontrolled hemorrhage and coagulopathy is responsible for over 50% of all trauma related deaths within the first 48hrs of admission. Coagulation profiles are not routinely done among trauma patients in resource limited settings and there is a paucity of data on acute traumatic coagulopathy (ATC) in sub Saharan Africa. The study was conducted to evaluate the prothrombin time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 17 publications
14
15
0
Order By: Relevance
“…RTIs still remain the leading cause of injuries (56.4%), a finding which is consistent with that of other trauma related studies [17,18]. There are observed associations between the mechanism of injury and the body region injured ( Table 2).…”
Section: Clinical Characteristicssupporting
confidence: 90%
See 2 more Smart Citations
“…RTIs still remain the leading cause of injuries (56.4%), a finding which is consistent with that of other trauma related studies [17,18]. There are observed associations between the mechanism of injury and the body region injured ( Table 2).…”
Section: Clinical Characteristicssupporting
confidence: 90%
“…Of the patients who presented within 1 hour of injury, 61.1% were in grade IV shock. This late hospital presentation is also observed in other studies [17,18]. This is likely to be due to: a long distance from hospital; lack of an organised pre-hospital care system which would facilitate early transfer of patients to the hospital; and poor communication due to lack of toll free functional emergency numbers.…”
Section: Duration From Time Of Injurysupporting
confidence: 70%
See 1 more Smart Citation
“…In Guinea, a study of 2829 victims of RTA during the year 2009 showed TBI to be present in 82% of cases with median age 27.1 years . In East Africa, a study from Uganda showed TBI to be the second reason for admission to an intensive care unit, with 1774 patients admitted over 7 years …”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Mujuni et al ., the prevalence of deranged aPTT was found to be 37% in patients of major trauma, which is much higher than the findings of the present study. [ 7 ]…”
mentioning
confidence: 99%